Pertanggungjawaban Perdata atas Penyalahgunaan Teknologi Deepfake terhadap Karya Visual Digital - Sari, Intan Mustika; Sudarwanto, Albertus Sentot (Indonesian Journal of Social Sciences and Humanities, 2026)
The development of artificial intelligence technology, particularly deepfake, has created new challenges in the protection of digital visual works as safeguarded under Law Number 28 of 2014 concerning Copyright. The misuse of deepfake technology that modifies or imitates digital visual works without the creator’s authorization has the potential to infringe upon the creator’s moral rights and economic rights, while specific regulations governing deepfake have not yet been explicitly regulated in Indonesian positive law. This research aims to analyze the form of civil liability for the misuse of deepfake technology against digital visual works based on the concept of unlawful acts. The research method employed is normative legal research using a conceptual approach. The results of the study indicate that the misuse of deepfake against digital visual works fulfills the elements of an unlawful act as stipulated in Article 1365 of the Indonesian Civil Code, namely the existence of an unlawful act, fault, damage, and a causal relationship. Although deepfake is a product of artificial intelligence technology, legal liability remains attached to humans as users and controllers of the technology. Therefore, the appropriate form of civil liability is individual liability based on the element of fault in the form of intent.